2008
DOI: 10.1007/s00401-008-0352-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of the human substantia nigra in ageing and Parkinson’s disease

Abstract: To investigate the relation between the loss of substantia nigra (SN) neurons in normal ageing and Parkinson's disease (PD), we measured the total number and the cell body volume of pigmented (neuromelanin) neurons in the SN. We examined young (n = 7, mean age: 19.9), middle-aged (n = grudow1@jhmi.edu. NIH Public Access NIH-PA Author ManuscriptNIH-PA Author Manuscript NIH-PA Author Manuscript 9, mean age: 50.1), and older controls from the Baltimore Longitudinal Study of Aging (n = 7, mean age: 87.6), as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
117
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(136 citation statements)
references
References 52 publications
15
117
0
4
Order By: Relevance
“…Our results are in agreement with those of Sasaki et al [15]. Additionally, we showed that the contrast ratio of the SNc was correlated with the Hoehn-Yahr stage of PD, which is in accordance with progressive neuromelanin loss during the course of the disease [25]. Consequently, this method is a potential biomarker for neurodegeneration in the SNc and LC of PD patients.…”
Section: Discussionsupporting
confidence: 82%
“…Our results are in agreement with those of Sasaki et al [15]. Additionally, we showed that the contrast ratio of the SNc was correlated with the Hoehn-Yahr stage of PD, which is in accordance with progressive neuromelanin loss during the course of the disease [25]. Consequently, this method is a potential biomarker for neurodegeneration in the SNc and LC of PD patients.…”
Section: Discussionsupporting
confidence: 82%
“…As for the mean age at death, PD and ILBD did not differ with respect to C, while PD differed vs ILBD, with the ILBD group being older. These findings substantiated the comparability of the mean age at death between ILBD and C, and reduced possible confounding effects due to aging 31 on the NNL measured in ILBD. No differences were observed for the mean PMI and BW across all 3 groups.…”
supporting
confidence: 70%
“…For instance, mTOR and Akt regulate cell mass and Akt has trophic actions on neurons including increasing their size and degree of sprouting (Ries et al, 2006) as well as the caliber and branching of axons (Markus et al, 2002). In PD, in contrast, there is a significant atrophy of pigmented SN neurons (Rudow et al, 2008). mTOR (Swiech et al, 2008) and Akt (Jaworski et al, 2005;Kumar et al, 2005) signaling pathways also play critical roles in dendritic arborization which is markedly reduced in neurons affected by PD (Patt and Gerhard, 1993;Kumar et al, 2005).…”
Section: Discussionmentioning
confidence: 99%